A 189-year tree-ring record of drought for the Dzungarian Alatau, arid Central Asia. (15th October 2017) - Zhang, Ruibo; Zhang, Tongwen; Kelgenbayev, Nurzhan; He, Qing; Maisupova, Bagila; Mambetov, Bulkajyr T.; Chen, Feng; Dosmanbetov, Daniyar; Shang, Huaming; Yu, Shulong; Yuan, Yujiang
Graphical abstract: Highlights: Tree rings provide a 189-year Palmer Drought Severity Index (PDSI) record for the Dzungarian Alatau, arid Central Asia. The reconstruction captures the extreme drought in 1917 and 1945. The climate changes include a notably wetting trend from 1980 to 2005, but drying after 2005. Abstract: Mountain systems are the most important sources of water in arid Central Asia (ACA). It is therefore essential to understand past cycles of droughts and pluvials and to explore how future cycles might influence the sustainable utilization of regional water resources. The Palmer Drought Severity Index (PDSI) is a widely applied measure of dryness that can be reconstructed from tree rings. Here, a Schrenk spruce ( Picea schrenkiana Fisch. et Mey) tree-ring chronology was developed for the Dzungarian Alatau of ACA. Correlation and response analysis indicated that the PDSI from previous July to current June was the principal factor limiting radial growth. The chronology was used to reconstruct the PDSI of the past 189 years for the Dzungarian Alatau. A calibration model for the period from 1950 to 2011 explains 42.6% (or 41.7% after adjusting for the loss of degrees of freedom) of the actual PDSI variance. The reconstructed PDSI might be representative of drought conditions for most of ACA because it captures severe drought events in the 1910s and 1940s that were widespread across ACA. The extreme drought years 1917 and 1945 are especially pronounced. A decadal analysis shows that the five periods in which the PDSI trend increased were 1830–1840s, 1880–1890s, 1920–1930s, 1950–1960s, 1980–2000s. The PDSI declined in the 1850–1870s, the 1900–1910s, the 1940s and the 1970s. The PDSI in ACA exhibited a notably long and rapid wetting from 1980 to 2005, but decreased after 2005. In fact, there have been three especially dry years (2008, 2014 and 2015) in the last 10 years. Meanwhile, there was large power in the 2.1-year, 2.9-year, 4.1-year, 5.5-year, 9.5-year and 10.8-year short periods and in the 30–40-year long periods.